UPAYA MENINGKATKAN PRESTASI BELAJAR PENDIDIKAN AGAMA ISLAM DENGANMENERAPKAN MODEL PEMBELAJARAN KOLABORASI PADA SISWA KELAS II SD NEGERI 4 KROMENGAN - Kurniawati, Linda; Sutiah, Sutiah; Tharaba, M. M. Fahim (Muta'allim: Jurnal Pendidikan Agama Islam, 2023)
This research is based on the problem of (a) How will PAI learning achievement increase by implementing the collaborative teaching model for class II students in the 2023/2024 academic year (b) What is the influence of the collaborative teaching model on PAI learning motivation for class II students in the 2023/2024 academic year. Meanwhile, the aims of this research are (a) to know the increase in PAI learning achievement after implementing the collaborative teaching model (b) to find out the effect of PAI learning motivation after implementing the collaborative teaching model. This research uses three rounds of action research. Each round consists of four stages, namely: planning, activities and observations, reflection and revision. The target of this research is class II students for the 2023/2024 academic year. The data obtained is in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis, it was found that student learning achievement increased from cycle I to cycle III, namely, cycle I (73.17%), cycle II (82.93%), cycle III (95.12%) Abstrak Penelitian ini berdasarkan permasalahan (a) Bagaimanakah peningkatan prestasi belajar PAI dengan diterapkannya model pengajaran kolaborasi pada siswa kelas II tahun pelajaran 2023/2024( b) Bagaimanakah pengaruh Model pengajaran kolaborasi terhadap motivasi belajar PAI pada siswa kelas II Tahun pelajaran 2023/2024. Sedangkan tujuan dari penelitian ini adalah (a) ingin mengetahui peningkatan prestasi belajar PAI setelah diterapkannya model pengajaran kolaborasi (b) Ingin mengetahui pengaruh motivasi belajar PAI setelah diterapkan model pengajaran kolaborasi. Penelitian ini menggunakan penelitian tindakan (action research) sebanyak tiga putaran. Setiap putaran terdiri dari empat tahap yaitu : rancanan, kegiatan dan pengamatan, refleksi dan refisi. Sasaran penelitian ini adalah siswa kelas II Tahun pelajaran 2023/2024 Data yang diperoleh berupa hasil tes formatif, lembar observasi kegiatan belajar mengajar. Dari hasil analis didapatkan bahwa prestasi belajar siswa mengalami peningkatan dari siklus I sampai siklus III yaitu, siklus I (73,17%), siklus II (82,93%), siklus III (95,12%)